Melanoma in the Eyes of Mechanobiology - Brás, M. Manuela; Radmacher, Manfred; Sousa, Susana R.; Granja, Pedro L. (Frontiers in Cell and Developmental Biology, 2020)
impaired by injury, genetic or chronic diseases. Among all skin diseases, melanoma is one 23 of the most severe, which can lead to death, due to the metastization process. 24 Mechanotransduction has a crucial role for invasion motility, adhesion and metastization 25 processes, since it deals with the response of cells to physical forces. It is important to explore 26 signalling pathways in order to understand how biophysical forces, produced or mediated by 27 the Extracellular Matrix (ECM), affect the interior of healthy and tumour cells. It is also 28 important to address how healthy cells and the ECM respond to forces caused by tumour 29 tissue. During these processes, several molecules (in the nucleus and cytoplasm) are activated 30 due to physical cues originating from the microenvironment. Melanocytes, keratinocytes, 31 fibroblasts and the ECM are the cells, which play a crucial role in melanoma formation. This 32 manuscript will address these components, considering their mechanical contribution and 33 relevance in this disease. The pigmentation of melanoma cells can also influence the 34 mechanical properties of these cells, which can be associated with changes in their stiffness. 35 These mechanical changes can be related with the migration, adhesion or invasiveness 36 potential of these cells promoting a high metastization capacity of this cancer. 37 Mechanosensing, mechanotransduction and mechanoresponse will be highlighted with 38 respect to the motility, invasion, , adhesion and metastization in melanoma cancer.